Measuring spinal motion in rowers: the use of an electromagnetic device - Bull, A. M.; McGregor, A. H. (Clinical Biomechanics, 2000)
Objective. To determine whether a skin-mounted electromagnetic measurement device can be used to measure lumbar spinal motion in rowers and discriminate between variations in technique.Design. The lumbar spinal kinematics of elite level rowers were assessed with an electromagnetic device (Flock of Birds) during ergometer training using five technique variants. The system was correlated with sagittal MRI imaging of the lumbar spine and pelvis.Background. Rowing technique is related to performance and injury. This study sought to test a method to obtain quantitative data on the effect of changes in technique on lumbar spinal and pelvic motion.Methods. Lumbar spinal and pelvic motion were measured in six elite level rowers on an ergometer using normal rowing technique, three common bad technique variants, and after a 10 min piece of rowing simulating fatigue.Results. Significant differences were found between the different rowing techniques for femoral, thoraco-lumbar and lumbo-sacral flexion.Conclusions. Kinematic parameters of spinal motion of rowers can be measured dynamically and used to quantify and discriminate between good and bad rowing styles.RelevanceThere is a consistent style of "good" rowing technique on an ergometer. Deviations from this technique can be measured and this will allow studies to be conducted comparing rowing styles between rowers of different standards and between different boat houses. There is potential to develop a dynamic feedback system to the rower that will assist in training and eradicate bad technique variants.